Maternal vaccination with live-attenuated Rift Valley fever virus protects offspring via immune transfer - Austin T. Hertel; Cynthia M. McMillen; Ryan M. Hoehl; Dominique J. Barbeau; Anita K. McElroy; Amy L. Hartman (npj Vaccines)
Abstract Rift Valley fever virus (RVFV) causes high rates of spontaneous abortions and neonatal mortality in ruminants resulting in severe socioeconomic and public health consequences. Maternal vaccination may protect pregnant animals, fetuses, and neonates via transfer of maternal antibodies; however, currently available live-attenuated RVFV vaccines are generally unsafe for use during pregnancy. RVFV-delNSs/NSm is a live attenuated strain that has demonstrated favorable safety and efficacy in pregnant livestock, yet studies investigating maternal vaccination as a strategy to protect neonates from RVF are limited. Using pregnant Sprague-Dawley rats, we show that maternal vaccination with RVFV-delNSs/NSm leads to efficient transfer of anti-RVFV antibodies to offspring. These offspring were completely protected from lethal RVFV challenge. Although further investigation is required in susceptible ruminant species, our findings indicate that maternal anti-RVFV immunity is sufficient to protect offspring, highlighting maternal vaccination as a potential strategy to reduce RVF disease burden in endemic regions.